Implementasi Kebijakan Tatap Muka Terbatas Sebagai Model Alternatif Pembelajaran Bahasa Arab di Era Pandemi Covid-19 - Apri Wardana Ritonga; Desriliwa Ade Mela; Aulia Mustika Ilmiani (IAI Muhammadiyah Sinjai, 2022)
Learning Arabic using a limited face-to-face model seems to find its momentum after online learning has been going on for a long time. Through this model, it is hoped that the difficulties in learning Arabic when online learning will be eroded. This study aims to describe the implementation of the limited face-to-face policy as an alternative model of learning Arabic in the Covid-19 pandemic era, student motivation, learning media used, and obstacles faced by students. The research method uses a case study with a qualitative descriptive approach at STAI Sabili Bandung. Data analysis techniques through the stages of reduction, presentation, and conclusion. While the validity of the data test using triangulation and data sources. The results of this study indicate that: first, students' motivation to follow the limited face-to-face learning model based on the Arabic learning achievement index which has decreased since online-based learning. Second, learning media used during limited face-to-face learning such as power points, supporting books, laptops, Lcd projectors, and various online media such as Youtube, E-learning, Gmail, Google Drive, and Websites. Third, the obstacles that arise when limited face-to-face learning comes from technical matters such as mobility to campus and non-technical in learning Arabic skills.